Telipogon pillaropatatensis (Oncidiinae) : a new species from the East-Central Andes of Ecuador - Iturralde, Gabriel Alfredo
A new species, Telipogon pillaropatatensis, is described from the highlands of east-central Ecuador. It is morphologically similar to T. octavioi but differs by having a corolla with longitudinal thick vein lines without reticulations and a column with three dense bundles of equally sized setae. Also, our phylogenetic analyses suggest that they are not closely related. Interestingly, among the analyzed taxa, T. pillaropatatensis appears to have a closer phylogenetic relationship with the highly distinct T. pulcher and T. hausmannianus than with the morphologically similar T. octavioi. The new species has been found in a relatively small area, covering just a few square kilometers in east-central Ecuador. Additionally, we documented remarkable variation in the coloration and size of the corolla. Information regarding the species' habitat, ecology, phylogenetic relationships, and conservation status is also provided.